Evaluation of Energy Alternatives through FAHP for the Energization of Colombian Insular Areas - Moreno Rocha, Christian Manuel; Domingue, Esnaider D. Florian; Castillo, Daniel A. Diaz; Vargas, Kevin Logreira; Guzman, Andres Alfredo Medina (International Journal of Energy Economics and Policy, 2022)
In this study, the methodology of the Analytical Hierarchy Process with fuzzy logic (FAHP) is implemented to provide decision criteria in the selection, planning and development of electric power generation projects from renewable energy sources in the insular regions of Colombia. In this study, six renewable energy sources were considered, biomass combustion, anaerobic digestion of biomass, biogas landfills, waste incineration, photovoltaic energy and hydrogen-generated energy, due to their energy potential in insular areas and not interconnected with the national electricity system. To determine the order of priority in the development of energy conversion technologies, a questionnaire was drawn up and sent to a group of experts. Given the need to generate electricity in a sustainable way, the information was analyzed under four main criteria: technical, environmental, social and economic. Sixteen additional subcriteria were selected based on a literature review. In general, the economic criterion is the most relevant in the area due to the high investment and operating costs of electricity generation. The social criterion highlights the opportunity to create new jobs very important for the study area, while the environmental criterion highlights the component of renewable energy substitution and environmental care, a key aspect in the diversification of the energy matrix, which is part of the country's political agenda. Regarding the technological component, self-consumption photovoltaic energy seems the most favorable due to its low environmental impact and the considerable price reduction experienced by the solar panel market in recent years.